All roads lead to ganga - Bond, Ruskin (New Delhi Rupa Publications, 2007)
The story of the Ganges, from her source to the sea, from old times to new, is the story of India's civilization and culture, of the rise and fall of empires, of great and proud cities, of adventures of man... Jawaharlal Nehru
Keywords: Anthology